The Role of Operational Efficiency and Credit Risk in Banking Profitability: Panel Data Evidence from Indonesian Listed Banks (2010-2024) - Yeti Rosita; Jaja Suteja; Atang Hermawan; Sugiyanto Sugiyanto (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
This study examines the effects of operational efficiency and credit risk on banking profitability in Indonesia, with inflation, capital adequacy, and the pandemic period included as control variables. The study addresses the limited empirical evidence on the comparative importance of internal bank-specific factors in explaining profitability among listed banks in an emerging market context. Using balanced panel data from 13 publicly listed banks in Indonesia over the period 2010–2024, this study applies a Random Effects Model with panel-corrected standard errors (PCSE) to address heteroskedasticity and cross-sectional dependence. Banking profitability is measured by return on assets (ROA), operational efficiency is proxied by the operating expenses to operating income ratio (BOPO), and credit risk is measured by non-performing loans (NPL). The results show that operational efficiency is the most dominant determinant of banking profitability, with BOPO having a strong negative and significant effect on ROA. Credit risk also negatively affects profitability, although its relative effect is smaller than operational efficiency. Inflation has a positive and significant effect, while capital adequacy and the pandemic period do not significantly affect profitability. These findings contribute to the banking profitability literature by demonstrating that internal cost efficiency plays a more decisive role than credit risk and crisis-related conditions in sustaining bank profitability. Practically, the study highlights the importance of cost structure optimization, digital process efficiency, and integrated credit risk management in strengthening bank performance and resilience.